2016
DOI: 10.2134/agronj2015.0430
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Modeling of Yield Components and Brown Rust Resistance in Sugarcane Families

Abstract: Sugarcane (Saccharum spp.) is a complex autopolyploid with high potential for biomass production that can be converted into sugar and ethanol. Genetic improvement is extremely important to generate more productive and resistant cultivars. Populations of improved sugarcane are generally evaluated for several traits simultaneously and in multi-environment trials. In this study, we evaluated two full-sib families of sugarcane (SR1 and SR2) at two locations and 3 yr for stalk diameter, stalk height, stalk number, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 81 publications
(119 reference statements)
0
36
0
3
Order By: Relevance
“…These cultivars have chromosome numbers ranging from 100 to 130, are vegetatively propagated, and result from the selection of populations derived from outcrossing heterozygous parents [1, 9]. Sugarcane has a very high photosynthetic efficiency and is a crop with major economic importance in many tropical and subtropical countries primarily because of its use in the production of sugar and bioethanol [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…These cultivars have chromosome numbers ranging from 100 to 130, are vegetatively propagated, and result from the selection of populations derived from outcrossing heterozygous parents [1, 9]. Sugarcane has a very high photosynthetic efficiency and is a crop with major economic importance in many tropical and subtropical countries primarily because of its use in the production of sugar and bioethanol [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…In the studies of sugarcane families of Moraes et al (2010), the results of CVg for TCH and TSH were very similar (19.51 and 19.56%), and lower for FIB, BRIX, and PC (1.46 to 5.08%). Balsalobre et al (2016) reported very close values for BRIX, PC, and FIB, and lower values for the traits TCH and TSH.…”
Section: Resultsmentioning
confidence: 87%
“…Os dois marcadores moleculares de diagnóstico, R12H16 e 9O20-F4-RsaI, fortemente associados ao gene Bru1 (25), foram utilizados para avaliar a presença do gene. A análise dos resultados foi feita comparando-se as respostas dos haplótipos dos marcadores com a avaliação a campo usando modelo misto linear generalizado, conforme proposto por Balsalobre et al (14).…”
Section: Análises Molecularesunclassified
“…A complexidade do genoma da cana-de-açúcar é devido ao seu elevado número de cromossomos, variando de 100 a 130 (8, 9); ao tamanho do genoma, com aproximadamente 10 Gb (10,11,12); e à ocorrência de aneuploidia, com um número variável de cromossomos em cada grupo de homeologia (13). Desta forma, a obtenção de variedades com alta performance agrícola torna-se um grande desafio (14,15,16,17).…”
Section: Introductionunclassified
See 1 more Smart Citation